Evaluation of a Soil-Based System to Dissipate Multiple Pesticides - Peacock, Aaron D.; Lytle, Cory A.; Hart, William E.; Yoder, Daniel C.; Mueller, Thomas C. (Remediation (New York, N.Y.), 2015)
Pesticide contaminated wastewater resulting from leftover mixes, equipment cleaning, and container disposal are problems related to pesticide use. This study reports on the effectiveness of a soil‐based bioreactor (SBBR) to dissipate pesticides of differing concentrations and mixtures. In order to accomplish this study, soil columns were used to simulate the SBBR. A mixture of five herbicides and two insecticides from seven different chemical families (atrazine, dicamba, fluometuron, metolachlor, sulfentrazone, chlopyrifus, and λ‐cyhalothrin) were added to the SBBR‐simulated system as formulated products in three concentrations each: 0 part per million (control), 10 ppm, and 100 ppm. Additionally a 1,000 ppm treatment was added that included just the five herbicides to investigate how the system would respond to heavy loading. The system was run for 90 days with samples taken at day 4 (just prior to loading the columns), then at 30, 60, and 90 days. At low pesticide concentrations (10 and 100 ppm), there was significant dissipation (p < 0.05) of all pesticides in the columns except sulfentrazone. At 1,000 ppm, fluometuron, in addition to sulfentrazone, did not show significant dissipation. Overall, the system performed as expected and could be considered practical for use on farms or nurseries. ©2015 Wiley Periodicals, Inc.